The effects of temperature and pressure on bubble repulsion from surfaces - Bidin, Noriah; Ahmad Sekak, Khirulnadim (2000)
In a real cavitation field, fluid pressures can vary, depending on the operating conditions, from near the fluid vapor pressure up to 100 atm near the collapse region of cavitation bubbles. At the same time substantial differences in temperature exist throughout such a system. Therefore it is important to establish the combined effects of pressure and temperature in studies of bubble repulsion in order to achieve a better understanding of protection methods for solid surfaces. A fundamental study of a single cavity induced by focused laser light has been carried out with high-speed photography. The temperature and the pressure of the test region were varied and the bubble repulsion on polyethylene foam was observed. The results of the investigation indicate that bubble repulsion decreases as the pressure in the test region increases. The distance of repulsion was found to be proportional to the fluid temperature.